A practical guide to creative writing in schools seven creative writing projects for ages 8-14 - Clark, Fiona (English teacher) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book contains seven tried-and-tested creative writing projects for pupils aged 8-14. Each project is delivered through a series of workshops and enables pupils to explore a literary genre or writing style, discuss themes and topics and receive constructive feedback about their writing. The projects cover topics such as identity, cultural heritage, tolerance, empathy, morality, dreams and much more. Teachers wanting to run creative writing projects will find this book easy to follow, practical and timesaving. Each project allows students to: explore a certain literary genre or writing style in detail be creative and have fun while learning think about, talk about and discuss themes and topics receive constructive feedback about their writing pursue their own ideas see themselves as real' writers with a real' audience understand that writing can be enjoyable, artistic and relaxing experience creativity to improve their wellbeing. These ready-made projects are invaluable for teachers who are looking for new and successful creative writing projects for a range of students. They will enable teachers to immediately start making a difference to their students' confidence and writing skills, allowing them to be as creative and imaginative as possible and use creativity as a springboard for their own writing.
OCLC-licensed vendor bibliographic record.
Keywords: Creative writing (Elementary education); Creative writing (Middle school); English language -- Composition and exercises -- Study and teaching (Elementary) -- Activity programs; English language -- Composition and exercises -- Study and teaching (Middle school) -- Activity programs; Project method in teaching; EDUCATION / Secondary; EDUCATION / Elementary; EDUCATION / Teaching Methods & Materials / General